Letramento emergente, consciência fonológica e leitura de alunos com deficiência intelectual no ensino regular - Barbosa, Esmeralda Aparecida de Oliveira (2014)
This study stems from an interest in examining the impact of school inclusion in terms of possible benefits of an academic nature, such as the acquisition of basic learning of reading for students with intellectual disabilities. The study aimed to examine the utilization of skills related to emergent literacy and basic skills of reading presented by a group of students with intellectual disabilities, attending the early elementary grades in regular rooms, and had the support of care specialized education provided in multifunctional features. Also sought to identify the expectations of the resource room s teacher and parents on the acquisition of academic learning by students. The sample consists of five students diagnosed with intellectual disability who attend regular classes of basic education and resource room. The data about the repertoire of reading and writing students were obtained through assessment instruments of knowledge and skills of emerging literacy, phonological awareness and reading and writing skills required in Basic Education. For three of the participants was used the Testing Colored Progressive Matrices Raven - General Scale, to obtain data about their intellectual level. Were used interviews to obtain data about the expectations and conditions relating to learning students' reading, presented by the resource room s teachers and family. The results indicate that students in the sample had familiarity with only a small portion and less critical of set components of emergent literacy and phonological awareness. Students no exhibited no familiarity with the skills of decoding individual words and texts, not reaching the minimum criteria for this stage of reading literacy. Also observed, in relation to the learning experiences of students in the resource room, they do not cover the promotion of relevant components for the acquisition of reading skills. We discuss the implications for the evaluation process and for teaching reading students with intellectual disabilities.